DNA copy-number measurement of genome replication dynamics by high-throughput sequencing: the sort-seq, sync-seq and MFA-seq family. - Batrakou, DG; Müller, CA; Wilson, RHC; Nieduszynski, CA (Nature Research, 2020)
Genome replication follows a defined temporal programme that can change during cellular differentiation and disease onset. DNA replication results in an increase in DNA copy number that can be measured by high-throughput sequencing. Here we present a protocol to determine genome replication dynamics using DNA copy-number measurements. Cell populations can be obtained in three variants of the method. First, sort-seq reveals the average replication dynamics across S phase in an unperturbed cell population; FACS is used to isolate replicating and non-replicating subpopulations from asynchronous cells. Second, sync-seq measures absolute replication time at specific points during S phase using a synchronized cell population. Third, marker frequency analysis can be used to reveal the average replication dynamics using copy-number analysis in any proliferating asynchronous cell culture. These approaches have been used to reveal genome replication dynamics in prokaryotes, archaea and a wide range of eukaryotes, including yeasts and mammalian cells. We have found this approach straightforward to apply to other organisms and highlight example studies from across the three domains of life. Here we present a Saccharomyces cerevisiae version of the protocol that can be performed in 7–10 d. It requires basic molecular and cellular biology skills, as well as a basic understanding of Unix and R.